Perfil motivacional de competidores de slackline - Pereira, Lucas Fraga (2020)
When analyzing the history timeline, in search of slackline origins, we found that people´s fascination for the art of balance accompanied the men´s development, and acquired new meanings throughout historical periods. In the Contemporary Age, we observe